1998
DOI: 10.1063/1.367173
|View full text |Cite
|
Sign up to set email alerts
|

Oriented diamond growth on silicon (111) using a solid carbon source

Abstract: Transmission electron microscopy analysis of the oriented diamond growth on nickel substrates Diamond films grown by hot filament chemical vapor deposition from a solid carbon source Textured diamond films have been grown on silicon ͑111͒ substrate by using hot filament chemical vapor deposition. A graphite plate immersed in hydrogen was used as the carbon source rather than the conventional gaseous methane source. During the nucleation period, a negative bias relative to the filaments was applied to the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[27][28][29] And the band at about 797 cm -1 originates from the transverse optical phonon mode of Si-C bonds formed during the original growth stage of diamond films. [29][30][31] It can also be seen that ( 100) diamond film has higher transmittance than (111) diamond film.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…[27][28][29] And the band at about 797 cm -1 originates from the transverse optical phonon mode of Si-C bonds formed during the original growth stage of diamond films. [29][30][31] It can also be seen that ( 100) diamond film has higher transmittance than (111) diamond film.…”
Section: Resultsmentioning
confidence: 84%
“…It is obviously observed that one-phonon absorption becomes stronger in the (100) diamond film than that in the (111) diamond film, which indicates that (111) diamond film has lower impurities and defects than (100) diamond film. In the FT-IR spectrum of (100) diamond film, the small absorption band at about 2830 cm -1 is associated with the C−H stretching vibration mode of diamond films. And the band at about 797 cm -1 originates from the transverse optical phonon mode of Si−C bonds formed during the original growth stage of diamond films. It can also be seen that (100) diamond film has higher transmittance than (111) diamond film. The high transmittance of (100) diamond film is related to the properties of (100) facet and the smooth surface.…”
Section: Resultsmentioning
confidence: 99%
“…At the forming intermediate 3C-SiC layer, the lattice mismatch between SiC and diamond is reduced: the lattice constant of 3C-SiC is 4.36 Å. Intermediate 3C-SiC layer, obtained during initial growth of diamond film via HFCVD from solid carbon source was discussed previously [2,43]. In these works the methods to modify SiC layer structure with bias applied are developed.…”
Section: Resultsmentioning
confidence: 98%
“…The problem of forming SiC layer on Si wafer is closely connected with initial stages of diamond heteroepitaxial growth [1]. The formation process and structure of intermediate SiC layer has been studied also by Woo et al [2]; the ability of SiC to form intermediate layer have also been observed by Thomas et al and Jiang et al., but only insignificant quantity of embedded SiC particles in amorphous layer or separate grains was found, that cannot account for the entire extended single-crystal diamond area [3,4]. The controlled formation of intermediate layer is the important subject of investigation.…”
Section: Introductionmentioning
confidence: 99%